FAKTOR-FAKTOR YANG DI PERTIMBANGKAN WISATAWAN MENGUNJUNGI OBJEK WISATA JATILUWIH-TABANAN - Ari Astana, I Made; Candra Dewi, Luh Komang; Budi Martini, Luh Kadek (Akademi Komunitas MAPINDO, 2020)
The purpose of this study is to analyze the factors considered by tourists in visiting the Jaliluwih-Tabanan Tourism Object. Respondents in this study were 85 tourists. The method of determining the sample purposive sampling, namely the sampling technique of data sources with certain considerations. The findings of this study are, the factors considered by tourists visiting the Jatiluwih-Tabanan Tourism Object, there are 5 factors, namely the first factor, namely the location factor has an eigenvalue of 4.384 and with a defining percentage variance value of 25.790%. The second factor, namely the brand factor has an eigenvalue of 3.201 and a variance percentage value of 18.827% which determines the perception of tourists to visit the Jatiluwih tourist attraction in Tabanan Regency. The third factor, namely the supporting factor has an eigenvalue of 1.939 with a percentage value of 11.408% variance which determines the perception of tourists to visit the Jatiluwih tourist attraction, Tabanan district. The fourth factor, namely the service factor has an eigenvalue of 1.248 with a variance percentage value of 7.342% which determines the perception of tourists to visit the Jatiluwih tourist attraction in Tabanan Regency. The fifth factor, namely the excellence factor of having an eigenvalue of 1.019 with a percentage value of 5.994% variance which determines the perception of tourists to visit Jatiluwih tourism objects, Tabanan regency. Keywords: Marketing Mix, Product Attributes, Consumer Purchasing Behavior, Tourist Decisions